Stereoselective synthesis of (−)‐cytoxazone and its unnatural congener (+)‐5‐epi‐cytoxazone. Issue 8 (1st July 2021) - Miranda, Izabel Luzia; dos Santos, Pedro Henrique Costa; Kohlhoff, Markus; Purgato, Gislaine Aparecida; Diaz, Marisa Alves Nogueira; Diaz‐Muñoz, Gaspar
Abstract: An interesting protocol for stereoselective synthesis of (−)‐cytoxazone and its unnatural stereoisomer (+)‐5‐ epi ‐cytoxazone from d ‐4‐hydroxyphenylglycine in overall yields of 10% and 16%, respectively, is described. The stereoselective addition of cyanide to an N ‐Boc protected aminoaldehyde ( tert ‐butyl (( R )‐1‐(4‐methoxyphenyl)‐2‐oxoethyl)carbamate) (5 ) constitutes the key step in this approach, producing a mixture of cyanohydrins 6a and b (1, 2‐ anti and 1, 2‐ syn tert ‐butyl (2‐cyano‐2‐hydroxy‐1‐(4‐methoxyphenyl)ethyl)carbamate) in 89% yield, with reasonable stereoselectivity (1.0:1.8) in favor of the anti ‐Felkin product (1, 2‐ syn ). A one‐pot sequence of three successive steps from this mixture produced the oxazolidinone isomers 9a and b ((4 R, 5 R )‐ and (4 R, 5 S )‐4‐(4‐methoxyphenyl)‐2‐oxooxazolidine‐5‐carboxylate). Chromatographic column separation and reduction of the ester function of both precursors led to (−)‐cytoxazone and (+)‐5‐ epi ‐cytoxazone. Abstract :